Discovery of Rare Mutations in Autism: Elucidating Neurodevelopmental Mechanisms - Gamsiz, Ece D. (Neurotherapeutics, 2015)
Autism spectrum disorder (ASD) is a group of highly genetic neurodevelopmental disorders characterized by language, social, cognitive, and behavioral abnormalities. ASD is a complex disorder with a heterogeneous etiology. The genetic architecture of autism is such that a variety of different rare mutations have been discovered, including rare monogenic conditions that involve autistic symptoms. Also, de novo copy number variants and single nucleotide variants contribute to disease susceptibility. Finally, autosomal recessive loci are contributing to our understanding of inherited factors. We will review the progress that the field has made in the discovery of these rare genetic variants in autism. We argue that mutation discovery of this sort offers an important opportunity to identify neurodevelopmental mechanisms in disease. The hope is that these mechanisms will show some degree of convergence that may be amenable to treatment intervention. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-015-0363-9) contains supplementary material, which is available to authorized users.